THE SIGNIFICANCE OF PERFORMING RACHMANINOFF'S 24 PRELUDES AS A CYCLE - Nakagawa, Eri (Mahidol Music Journal, 2023)
Sergei Rachmaninoff wrote Prelude, Op. 3, No. 2; 10 Preludes, Op. 23; and 13 Preludes, Op. 32 in all 24 different keys, following the trend of his Russian contemporary composers such as Felix Blumenfeld, Anton Arensky, Alexander Scriabin, C sar Cui, and Reinhold Gli re. Although Rachmaninoff's 24 Preludes, Op. 3, No. 2; Op. 23; and Op. 32 were written at three different periods in 1892, 1903 and 1910 respectively, the complete cycle of all 24 Preludes was published in a single volume in 1911. Unlike the systematic order in the sets of Johann Sebastian Bach's The Well-Tempered Clavier and Fr d ric Chopin's 24 Preludes, Op. 28, the key organization of Rachmaninoff's 24 Preludes seems random at first glance; however, they are uniquely integrated by the cyclical manipulation of tonal and rhythmic relationships and thematic ideas. This article reveals the significance of performing the 24 Preludes as a cycle by focusing on the following aspects: key scheme; use of common tones; anticipation of opening material at the end of the preceding prelude; use of the interval of a second; use of chromaticism; use of bell-like tones; cyclical use of two motives of Op. 3, No. 2; organization of tempi in Op. 23; and use of rhythms and compound meters in Op. 32.